Penerapan Sistem iREC Guna Mendukung Kegiatan Penelitian Ilmiah Pada Perguruan Tinggi - Susanto Rahardja; Muhamad Yusup; Nofia Supriyani (Universitas Raharja, 2013)
Technological developments that were increasingly rapidly, especially information technology have a positive impact in people’s lives. So spur of information technology to transform follow any changes that occur, due to the increasing needs of the growing. However, there are still problems to deal with at this point, including the benefit of the project are felt still less effective and efficient in the entire college community, thereby inhibiting the activities and some decision-making. Therefore, making an application system which is precise and accurate information is highly recommended. With online based storage system, it can greatly facilitate students learning environment. iREC is an online support system in the delivery of students’ project activities and scientific research, which strongly supports the iLearning environment and community. Further described in this article, regarding the problems that arise and solving the problem under study. In addition there are three (3)characteristics and 6 (six) advantages of this application. In the implementation, there are prototype displayed shown in iREC applications. Hence, it can be concluded that the contribution of iREC system can maximize scientific research activities in delivering a project to study of the students, so that more targeted research can be achieved, and can be used as a medium of valid information is for the entire university community and society in general.